2011
DOI: 10.2169/internalmedicine.50.5492
|View full text |Cite
|
Sign up to set email alerts
|

Significance of High HDL Cholesterol Levels in Japanese Men with Metabolic Syndrome

Abstract: Objective The objective was to clarify the significance of high high-density lipoprotein cholesterol (HDL-C) levels in the metabolic syndrome (MetS). The evaluation focused on insulin resistance as an indicator of early-stage MetS. Methods and Subjects Of 2705 men who first underwent an annual health check-up at Tokai University Hachioji Hospital, 2129 men were included in this study, after exclusion of those on medication for hypertension, diabetes or dyslipidemia, and those with a prior history of ischemic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…In the low-risk group, most clinical indicators except HDL cholesterol and fasting glucose were significantly improved. This is consistent with the results of studies of patients with type 2 diabetes 9,10,17 in which HbA 1C levels improved. Also, other studies targeting hypertension and obesity reported significant results regarding lipid profiles.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the low-risk group, most clinical indicators except HDL cholesterol and fasting glucose were significantly improved. This is consistent with the results of studies of patients with type 2 diabetes 9,10,17 in which HbA 1C levels improved. Also, other studies targeting hypertension and obesity reported significant results regarding lipid profiles.…”
Section: Discussionsupporting
confidence: 91%
“…An improvement in HDL was not consistent with results from this study. The previous study 18 emphasized lifestyle, especially smoking, exercise and alcohol consumption, as major contributors to increased HDL among 2129 men with metabolic syndrome. However, our education group sessions included general topics such as hypertension, hyperlipidaemia and diabetes management.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the possibility of intervention not only for subjects with high LDL-C and MDA-LDL levels who have already developed CAD but also for those with low LDL-C and high MDA-LDL levels who show no signs of atherosclerosis. Low HDL-C level is associated with the following characteristics: being overweight or obese [27][28][29], smoking [28,30], and weight loss [27]. Smoking cession [31] and regular aerobic exercise increases HDL-C levels [28,29,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Low HDL-C level is associated with the following characteristics: being overweight or obese [27][28][29], smoking [28,30], and weight loss [27]. Smoking cession [31] and regular aerobic exercise increases HDL-C levels [28,29,32,33]. Besides reversing cholesterol transport, the antioxidant properties of HDL may also play a major role in protection against the development of atherosclerosis [34].…”
Section: Discussionmentioning
confidence: 99%
“…These particles can be separated into two main subfractions, HDL2 and HDL3, based on their density after ultracentrifugation 7) , and both have been reported to exhibit inverse associations with the incidence of CVD 8) . We previously demonstrated the importance of analyzing levels of HDL-C subclasses, as well as overall HDL-C, when evaluating an individual's lifestyle habits [9][10][11] , insulin resistance, and MetS 12) . HDL2-C levels are associated with alcohol consumption, waist circumference (WC), smoking, and exercise.…”
Section: Introductionmentioning
confidence: 99%